2004
DOI: 10.1162/089892904322755638
|View full text |Cite
|
Sign up to set email alerts
|

Functional Parcellation of Attentional Control Regions of the Brain

Abstract: Abstract& Recently, a number of investigators have examined the neural loci of psychological processes enabling the control of visual spatial attention using cued-attention paradigms in combination with event-related functional magnetic resonance imaging. Findings from these studies have provided strong evidence for the involvement of a fronto-parietal network in attentional control. In the present study, we build upon this previous work to further investigate these attentional control systems. In particular, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
168
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(188 citation statements)
references
References 53 publications
19
168
1
Order By: Relevance
“…Our findings suggest that individuals lower in nicotine dependence have activation in these regions following exposure to smoking cues, which is consistent with another study showing lighter smokers to bias attention to smoking cues compared to both heavy smokers and nonsmokers (Hogarth et al, 2003). These brain regions have been associated with a broad range of processes including face processing (FG; Puce et al, 1996), memory (PHG; Hayes et al, 2007), attention (parietal cortex; Woldorff et al, 2004), and language (temporal cortex; Bookheimer, 2002) but not reward, motivational, and/or emotional information processing. Thus, greater activation …”
Section: Nicotine Dependencesupporting
confidence: 90%
“…Our findings suggest that individuals lower in nicotine dependence have activation in these regions following exposure to smoking cues, which is consistent with another study showing lighter smokers to bias attention to smoking cues compared to both heavy smokers and nonsmokers (Hogarth et al, 2003). These brain regions have been associated with a broad range of processes including face processing (FG; Puce et al, 1996), memory (PHG; Hayes et al, 2007), attention (parietal cortex; Woldorff et al, 2004), and language (temporal cortex; Bookheimer, 2002) but not reward, motivational, and/or emotional information processing. Thus, greater activation …”
Section: Nicotine Dependencesupporting
confidence: 90%
“…We found that BOLD signals in IPS, FEF, and SEF, cortical areas associated with modulating attentional signals (Corbetta et al, 1998;Kastner et al, 1999;Hopfinger et al, 2000;Giesbrecht et al, 2003;Woldorff et al, 2004), were also negatively correlated with behavior improvement. This result suggests an involvement of attention in perceptual learning in the current study, as has been demonstrated by several previous psychophysical studies.…”
Section: Changes In Attention-related Areas During Perceptual Learningmentioning
confidence: 79%
“…11) is consistent with the notion that the frontoparietal network exerts top-down control. Imaging studies of attention have shown the precuneus and midcingulate cortex to be coactivated with the IPS and lateral frontal cortex (36). A study by Woldorff et al (36) showed that the IPS (coordinates: L, Ϫ28, Ϫ62, 41; R, 32, Ϫ61, 45) and lateral frontal cortex (coordinates: L, Ϫ48, 3, 43; R, 46,6,43) were active when a cue was interpreted but attention was not shifted, whereas the precuneus was only active when attention was shifted.…”
Section: Discussionmentioning
confidence: 99%